Redefinicje demokracji w dobie międzywojennego kryzysu parlamentaryzmu w polskiej myśli polityczno-prawnej – przyczynek do badań - Wojtacki, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article discusses the influence of systemic changes occurring in Europe in the interwar period on the evolution of the notion of democracy in the Polish politico–legal thought. The analysis of works then created in the Polish scientific and political communities demonstrated the fact that the awareness of the crisis of parliamentary cabinet system was present among the Polish researchers and politicians at the same time when the research on this subject was conducted in the Western Europe by, among others, Joseph Barthelemy and Carl Schmitt. It allowed the author to show the process of redefining democracy in the political and social dimension, the result of which was the replacement of liberal democracy by a model of social democracy, being a formula of organizing the society around the elite delegated through the indirect election. The aim of the article was also to outline more extensive research perspective on the development of politico–legal sciences in the Second Polish Republic taking changes in defining the classical metapolitical notion, i.e. democracy as a point of reference.
Keywords: demokracja; parlamentaryzm; liberalizm; elityzm; autorytaryzm